1997
DOI: 10.1021/bk-1995-0611.ch010
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Properties of Halon Substitutes

Abstract: Halon fire extinguishing agents are used throughout the world to protect valuable electronics, oil and gas production operations, military systems, as well as a number of other critical facilities. Unfortunately, halons deplete stratospheric ozone, causing destruction at 3 to 16 times the rate of CFC-11 (a common refrigerant). As a consequence, the production of halons was prohibited on December 31, 1993 by an international treaty, the Montreal Protocol. This ban on halon production resulted in a search for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Acute toxicity. A 4 h exposure of rats to levels of 110,000 and 800,000 ppm of HFC 227ea did not cause mortality (Skaggs et al 1995).…”
Section: Subchronic and Chronic Toxicity A Few Studies Have Indi-mentioning
confidence: 83%
See 2 more Smart Citations
“…Acute toxicity. A 4 h exposure of rats to levels of 110,000 and 800,000 ppm of HFC 227ea did not cause mortality (Skaggs et al 1995).…”
Section: Subchronic and Chronic Toxicity A Few Studies Have Indi-mentioning
confidence: 83%
“…Exposure of Wistar rats to levels of 50,000 ppm of HFC 227ea, for 6 h/day, 5 days/week for 4 weeks did not result in any observable signs of toxicity. It was also reported that exposure of rats to a level of 105,000 ppm did not cause adverse effects (Skaggs et al 1995).…”
Section: Subchronic and Chronic Toxicity A Few Studies Have Indi-mentioning
confidence: 96%
See 1 more Smart Citation
“…Smoke and CO induce high levels of carboxyhemoglobin in the bloodstream, resulting in incapicitation or death. Approximate lethal concentrations (ALCs) for a 15-min exposure to HBr, HF, and COF 2 are 4750, 2500, and 1500 ppm, respectively (Skaggs et al 1995). With the advent of sophisticated models of enclosure fires and detailed reaction mechanisms, more attention is now being paid to the prediction of the formation rates of toxic compounds in fires.…”
Section: Introductionmentioning
confidence: 99%